Oxide based non-volatile resistance random access memory - Zheng, Ke (2015)
As one of the potential candidates for next generation non-volatile memory, resistance random access memory (RRAM) has attracted great attention recently. The study of resistive switching (RS) phenomenon could retrospect from 1960s and in nowadays various materials and structures have been gradually explored to fabricate RRAM devices. Transition metal oxides outstand in many aspects over other materials due to their relatively deposition process and stable RS performance. In this thesis, we firstly brief the history and development of RRAM research, including the material and fabrication issue, the operating mechanism and the industrial integration scheme. Then, our work focuses on several highly concerned issues of RRAM: developing transparent RRAM device based on economic and effective materials, reducing or avoiding Joule heating in filament based RRAM device to improve RS property and adjusting intrinsic defects in oxide to obtain more endurable and stable RS performance. By depositing GZO and ZnO on glass wafer, transparent RRAM cells without indium were constructed. This device with bipolar resistive switching behavior performs well in both endurance and retention test. The switching process could be understood by applying the filament model. The two resistance states, HRS and LRS, correspond to the connecting filamentary paths and broken ones within the bulk materials, which is controlled by the migration of oxygen vacancies. Compliance current should be properly applied in set operation or the device will be unable to reset. Joule heating plays a dual role in resistive switching, which can both strengthen the formed filaments in set process and accelerates the annihilation of filaments in reset process. A unidirectional bipolar RS was observed in the In/GaOx/NiOx/ITO heterostructure fabricated by magnetron sputtering at room temperature. The RS behavior could be concluded as the switching between rectifying and Ohmic behavior of the diode. The migration of intrinsic defects (oxygen vacancies in GaOx and oxygen ions in NiOx) alters the barrier, which accounts for the RS behavior observed. This design relies on interface type RS and offers an alternative scheme to reduce side effect in filament. The scaling potential is also examined by reducing the device size to 1 μm, where we observed that the switching current was reduced and switching windows was increased. The device shows good endurance and retention performance, manifesting the potential application of p-n junction structure in non-volatile memory. ZnO, Ga2O3 and NiO were introduced into TaOx to make a comparison on RS property. Among them, the ZnTaOx sample exhibited evident improvement of RS performance, including better endurance, smaller operating voltage and more stable resistance distribution. The improved behavior mainly attributes to the introduction of more intrinsic defects such as oxygen vacancies by mixing TaOx with ZnOx, which facilitates the filament-based RS. The I-V characteristics were also investigated to further clarify the variation of conduction induced by different mixtures. This experiment offers an alternative way to engineer the intrinsic defects in oxide and enhance the RS performance. In summary, the thesis addresses three parts of work on improving current RRAM subjects. ZnO and its variants were applied in transparent RRAM device. Interface type RS was constructed by utilizing p-n heterojunction stacks, which facilitate to reduce negative Joule heating effect. An effective way to adjust intrinsic defects of oxide and improve RS performance was demonstrated by mixing different oxide in certain ratio.